2021
DOI: 10.1016/j.heliyon.2021.e07540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal zinc supplementation or zinc status on pregnancy complications and perinatal outcomes: An umbrella review of meta-analyses

Abstract: Zinc is an essential trace element involved in different physiological functions. During pregnancy, it plays a crucial role in healthy embryogenesis. This umbrella review, therefore, aimed to summarize the existing literature of meta-analyses evaluating the effect of maternal zinc supplementation or zinc status on maternal and neonatal outcomes. Two databases, PubMed and Scopus, were selected to search the available literature without any temporal restriction. The literature search was performed during October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Cochrane database reviewed the role of zinc supplementation in 14% reduction of preterm birth (risk ratio (RR) 0.86, 95% confidence interval (CI) 0.76 to 0.97 in 16 randomized controlled trials (RCTs); 16 trials of 7637 women from low‐ and middle‐income settings with a high prevalence of zinc deficiency and perinatal mortality 106 . This is consistent with the findings of Terrin et al 27 Recent review by Iqbal and Ali 107 also found a significant relationship between low maternal zinc status and risk of pregnancy complications. Preterm babies, who are born with low zinc stores and with diminished capacity for zinc absorption and retention, could benefit from zinc supplements as an easily implemented intervention for growth, immune function and decreased morbidity 108 .…”
Section: Zinc Supplementation and Preterm Birthsupporting
confidence: 64%
“…Cochrane database reviewed the role of zinc supplementation in 14% reduction of preterm birth (risk ratio (RR) 0.86, 95% confidence interval (CI) 0.76 to 0.97 in 16 randomized controlled trials (RCTs); 16 trials of 7637 women from low‐ and middle‐income settings with a high prevalence of zinc deficiency and perinatal mortality 106 . This is consistent with the findings of Terrin et al 27 Recent review by Iqbal and Ali 107 also found a significant relationship between low maternal zinc status and risk of pregnancy complications. Preterm babies, who are born with low zinc stores and with diminished capacity for zinc absorption and retention, could benefit from zinc supplements as an easily implemented intervention for growth, immune function and decreased morbidity 108 .…”
Section: Zinc Supplementation and Preterm Birthsupporting
confidence: 64%
“…Several studies have also discovered that mothers who give birth to babies with LBW tend to have lower serum zinc levels than mothers who give birth to babies with normal birth weight; in this case, the lower maternal serum zinc levels are positively associated with lower birth weight [40]. A study which was carried out by Iqbal demonstrated a significant relationship between maternal zinc levels and the risk of pregnancy complications [41].…”
Section: Serum Zinc Levels For Pregnant Womenmentioning
confidence: 99%
“…This result in line acwith the theory which states that animal foods do not contain a lot of phytates so that zinc can be absorbed optimally. Fiber and phytic acid will inhibit zinc bioavailability (Iqbal and Ali, 2021).…”
Section: Discussion a Correlation Between Zinc Intake With Hemoglobin...mentioning
confidence: 99%